Learning models and media used by lecturers at labuhanbatu al washliyah university and al bukhary school of tarbiyah science (stita) labuhanbatu north sumatra during the covid-19 pandemic and new normal - wita ferwati; Fitri Endang Srimulat; Shabrina Rasyid Munthe; Dwina Putri (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
The research aims to describe and analyze the learning media used at two universities located in Rantauprapat City during the pandemic and New Normal, namely at Al Washliyah Labuhanbatu University and Tarbiyah Al Bukhary School of Science (STITA) Labuhanbatu, North Sumatra. This research method is a qualitative descriptive method for respondents in this study, lecturers at Al Washliyah Labuhanbatu University, and lecturers who teach at the Tarbiyah Al Bukhary College of Science (STITA) Labuhanbatu, North Sumatra. Data collection techniques in this study were carried out using questionnaires and interviews with lecturers who teach at two universities in the city of Rantauprapat. Based on data processing, it was concluded that the results of the study showed that the learning model used was Online during Covid-19 and the Blended Learning learning model, a Learning project, during the New Normal period. Teaching lecturers use learning media and remote communication media using Google Meet, Google Classroom, zoom, and WhatsApp. Based on the results of interviews with lecturers at Al Washliyah Labuhanbatu University and lecturers who teach at the Tarbiyah Al Bukhary College of Science (STITA) stated that the difficulties experienced during the pandemic and the New Normal in the learning process were internet access, lecturer skills in using media and creating media e-learning based.